(untitled) (MAUSAM, 1990)
Growth and decay rates as well as the durations of convective clouds in the Delhi region have studied using radar observations of such clouds, made during the pre-monsoon and monsoon seasons of 1980 to 1982. Vertical growth rates of radar echoes from such clouds varied between 1.0 and 25. 0 m/sec during pre-monsoon and between 0.9 and 12.8 m/sec during the monsoon season. Decay rates of the echoes are found to vary between 0.6 and 10.4 m/sec, and between 0.9 and 15.3 m/sec in these two seasons respectively. No significant difference was found between the average durations of the echoes in the pre-monsoon and monsoon seasons (39 and 36 minutes respectively). The mechanisms of precipitation initiation involved in these clouds have also been investigated and discussed in the paper.